Klasyfikacja obszarów wiejskich podregionu szczecińskiego pod względem sytuacji na rynku pracy - Sompolska-Rzechuła, Agnieszka (The Classification of Village Areas of Szczecin Subregion in Respect of Labour Market Situation, 2005)
The aim of this work is determination of village areas of Szczecin sub-region of zachodniopomorskie province in respect of labour market situation. Two taxonomic methods are used - agglomerative and iterative. Performed studies result in villages community division onto four classes, which are categorized in respect of adopted diagnostic characteristics. In the set of diagnostic variables mainly characteristics concerning women situation as economic activity factor and employment factor in village areas are taken into consideration. Ali calculations are performed with Statistica software.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 280-284